Method for preparing lightweight material mortar from coal gasification slag
Through steps such as crushing, screening, separation, acid -base treatment, and burning of gas -based slag, the silicon aluminum microfin beaded and prepared lightweight mortar to solve the problem of low utilization rate of gasification slag. Efficient use and environmental performance improvement.
Patent Information
- Application Number
- CN202411580228.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the utilization rate of coal gasification slag is relatively low, and the traditional treatment methods are mostly landfill or stacking, resulting in waste of land resources and environmental pollution.
Through the steps of crushing, screening, gravity spin, acid -soluble treatment, alkaline -soluble pore diameter, and burning treatment, the silicon and aluminum micro -beads in the gasized residue are extracted, and lightweight material mortar is prepared.
The efficient resource utilization of gas scum is realized, the emissions of solid waste are reduced, and the prepared light material mortar has light, high -strength, good thermal insulation performance, and is suitable for construction and thermal insulation.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waste resource utilization, and specifically relates to a method for preparing lightweight material mortar from coal gasification slag. Background Art
[0002] The gasification slag produced during coal gasification is a solid waste containing a large amount of residual carbon and glassy silica-alumina microspheres. These silica-alumina microspheres have potential application value in many fields due to their unique physical and chemical properties.
[0003] However, the current utilization rate of gasification slag is low, and traditional treatment methods are mostly landfill or stacking, which not only occupies land resources but also may cause environmental pollution.
[0004] In recent years, with the enhancement of environmental awareness and the development of resource utilization technology, how to utilize gasified slag efficiently and environmentally friendly has become a research hotspot. The present invention aims to provide a method for extracting silicon beads from gasified slag and preparing lightweight material mortar to realize resource utilization of gasified slag.
[0005] Based on this, a method for preparing lightweight material mortar using coal gasification slag was designed. Summary of the invention
[0006] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a method for preparing lightweight material mortar from coal gasification slag, which effectively solves the problems raised in the above background.
[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing lightweight material mortar from coal gasification slag, comprising the following steps:
[0008] Step S1, raw material preparation:
[0009] Selecting a certain amount of coal gasification slag as raw material;
[0010] Step S2, preliminary crushing and screening:
[0011] The fumed slag is initially crushed by a crusher to a particle size of 5-20 mm. Subsequently, the crushed fumed slag is classified according to the particle size using a vibrating screen or airflow classification technology to separate larger particles of residual carbon and smaller particles of a mixture of silicon-aluminum microbeads;
[0012] Step S3, gravity cyclone separation:
[0013] The classified gasified slag fine powder is added with water to prepare a slurry with a solid content of 15-25wt%, and stirred at a rotation speed of 1800-2500r / min for 40-60min. Then, the slurry is treated by a gravity cyclone separation device to separate the residual carbon and larger particles of the heavy components and the silicon-aluminum microbeads of the light components, so as to obtain a slurry rich in silicon-aluminum microbeads;
[0014] Step S4, acid dissolution treatment:
[0015] The slurry rich in silica-alumina microbeads obtained in step S3 is mixed with an appropriate amount of acid solution, the solid content in the mixed slurry is controlled to be 10-40wt%, the acid concentration is 5-20wt%, and the mixture is stirred and reacted at a temperature of 50-80°C for 2-4h to remove some metal oxide impurities in the silica-alumina microbeads and leave a mesoporous structure. After the reaction is completed, solid-liquid separation is performed, and the product is washed with deionized water until it is neutral to remove residual acid solution;
[0016] Step S5, alkali dissolution to adjust pore size:
[0017] Add an appropriate amount of alkaline solution to the solid material after the acid dissolution treatment in step S4 for alkaline dissolution reaction, the concentration of the alkaline solution is controlled at 0.1-5.0wt%, the reaction temperature is room temperature to 60°C, and the reaction time is 2-6h to further adjust the pore size structure of the microbeads. After the reaction is completed, solid-liquid separation, washing and drying are performed to obtain mesoporous silica microbeads with controllable pore size;
[0018] Step S6, calcination treatment:
[0019] The silicon microbeads after the alkali dissolution treatment in step S5 are calcined at a temperature of 550-750° C. for 2-4 hours to remove residual carbon components and improve the purity of the silicon microbeads;
[0020] Step S7, preparing lightweight material mortar:
[0021] Add 20-50 parts of the silicon beads calcined in step S6, 30-70 parts of other lightweight aggregates, 10-30 parts of cement, 0.1-5 parts of admixtures, and an appropriate amount of water into a mixer and mix well to obtain lightweight material mortar.
[0022] Preferably, in step S2, the particle size of the residual carbon is greater than 10 mm, and the particle size of the silica-alumina microbead mixture is less than 10 mm.
[0023] Preferably, in step S4, the acid solution is one of hydrochloric acid or nitric acid aqueous solution.
[0024] Preferably, in step S5, the alkaline solution is one of sodium hydroxide or potassium hydroxide aqueous solutions.
[0025] Preferably, in step S7, the other lightweight aggregate is one of perlite and vermiculite, and the admixture is one of a water reducer and a retarder.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention realizes efficient resource utilization of gasified slag and reduces the emission of solid waste; in addition, the present invention not only solves the problem of gasified slag stacking and pollution, but also promotes the recycling of resources, and has good economic and social benefits;
[0028] 2. The prepared lightweight material mortar has the characteristics of light weight, high strength, good thermal insulation performance, good physical properties and environmental protection performance, and can be used in construction, insulation and other fields;
[0029] 3. The process is simple and easy for industrial production. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] The present invention provides a method for preparing lightweight material mortar from coal gasification slag, comprising the following steps:
[0032] Step S1, raw material preparation:
[0033] Selecting a certain amount of coal gasification slag as raw material;
[0034] Step S2, preliminary crushing and screening:
[0035] The fumed slag is initially crushed by a crusher to a particle size of 5-20 mm. Subsequently, the crushed fumed slag is classified according to the particle size using a vibrating screen or airflow classification technology to separate larger particles of residual carbon and smaller particles of a mixture of silicon-aluminum microbeads;
[0036] Step S3, gravity cyclone separation:
[0037] The classified gasified slag fine powder is added with water to prepare a slurry with a solid content of 15-25wt%, and stirred at a rotation speed of 1800-2500r / min for 40-60min. Then, the slurry is treated by a gravity cyclone separation device to separate the residual carbon and larger particles of the heavy components and the silicon-aluminum microbeads of the light components, so as to obtain a slurry rich in silicon-aluminum microbeads;
[0038] Step S4, acid dissolution treatment:
[0039] The slurry rich in silica-alumina microbeads obtained in step S3 is mixed with an appropriate amount of acid solution, the solid content in the mixed slurry is controlled to be 10-40wt%, the acid concentration is 5-20wt%, and the mixture is stirred and reacted at a temperature of 50-80°C for 2-4h to remove some metal oxide impurities in the silica-alumina microbeads and leave a mesoporous structure. After the reaction is completed, solid-liquid separation is performed, and the product is washed with deionized water until it is neutral to remove residual acid solution;
[0040] Step S5, alkali dissolution to adjust pore size:
[0041] Add an appropriate amount of alkaline solution to the solid material after the acid dissolution treatment in step S4 for alkaline dissolution reaction, the concentration of the alkaline solution is controlled at 0.1-5.0wt%, the reaction temperature is room temperature to 60°C, and the reaction time is 2-6h to further adjust the pore size structure of the microbeads. After the reaction is completed, solid-liquid separation, washing and drying are performed to obtain mesoporous silica microbeads with controllable pore size;
[0042] Step S6, calcination treatment:
[0043] The silicon microbeads after the alkali dissolution treatment in step S5 are calcined at a temperature of 550-750° C. for 2-4 hours to remove residual carbon components and improve the purity of the silicon microbeads;
[0044] Step S7, preparing lightweight material mortar:
[0045] Add 20-50 parts of the silicon beads calcined in step S6, 30-70 parts of other lightweight aggregates, 10-30 parts of cement, 0.1-5 parts of admixtures, and an appropriate amount of water into a mixer and mix well to obtain lightweight material mortar.
[0046] In step S2, the particle size of the residual carbon is greater than 10 mm, and the particle size of the silica-alumina microbead mixture is less than 10 mm.
[0047] In step S4, the acid solution is one of hydrochloric acid or nitric acid aqueous solution.
[0048] In step S5, the alkaline solution is a sodium hydroxide or potassium hydroxide aqueous solution.
[0049] In step S7, the other lightweight aggregate is one of perlite and vermiculite, and the admixture is one of a water reducing agent and a retarder.
[0050] Embodiment 1:
[0051] A method for preparing lightweight material mortar from coal gasification slag, comprising the following steps:
[0052] Step S1, selecting a certain amount of coal gasification slag as raw material;
[0053] Step S2: The gasified slag is preliminarily crushed into a particle size of 5-20 mm by a crusher, and then sieved by a vibrating screen to separate the residual carbon with a particle size of more than 10 mm and the silicon-aluminum microbead mixture with a particle size of less than 10 mm;
[0054] Step S3: adding water to the classified gasified slag fine powder to prepare a slurry with a solid content of 20 wt%, stirring at a rotation speed of 2000 r / min for 50 min, and then separating the heavy components (residual carbon and larger particles) and the light components (silica-alumina microbeads) in the slurry by a gravity cyclone separation device to obtain a slurry rich in silica-alumina microbeads;
[0055] Step S4: mixing the slurry rich in silica-alumina microbeads with a hydrochloric acid aqueous solution, controlling the solid content in the mixed slurry to be 25wt% and the hydrochloric acid concentration to be 10wt%, stirring the reaction at a temperature of 60°C for 3h, and after the reaction is completed, performing solid-liquid separation, and washing the product with deionized water until it is neutral;
[0056] Step S5: adding the solid material after acid dissolution treatment to a sodium hydroxide aqueous solution for alkaline dissolution reaction, wherein the concentration of the sodium hydroxide solution is controlled at 1.0wt%, the reaction temperature is room temperature, and the reaction time is 4h. After the reaction is completed, solid-liquid separation, washing and drying are performed to obtain mesoporous silica microbeads with controllable pore size;
[0057] Step S6: calcining the silicon microbeads after the alkali dissolution treatment at a temperature of 600° C. for 3 hours;
[0058] Step S7: Add 30 parts of calcined silicon beads, 50 parts of perlite, 20 parts of cement, 1 part of water reducer and an appropriate amount of water into a mixer and mix well to obtain a lightweight material mortar.
[0059] Embodiment 2:
[0060] A method for preparing lightweight material mortar from coal gasification slag, comprising the following steps:
[0061] Step S1, selecting a certain amount of coal gasification slag as raw material;
[0062] Step S2: The gasified slag is preliminarily crushed into a particle size of 5-20 mm by a crusher, and then sieved by a vibrating screen to separate the residual carbon with a particle size of more than 10 mm and the silicon-aluminum microbead mixture with a particle size of less than 10 mm;
[0063] Step S3: adding water to the classified gasified slag fine powder to prepare a slurry with a solid content of 20 wt%, stirring at a rotation speed of 2000 r / min for 50 min, and then separating the heavy components (residual carbon and larger particles) and the light components (silica-alumina microbeads) in the slurry by a gravity cyclone separation device to obtain a slurry rich in silica-alumina microbeads;
[0064] Step S4: mixing the slurry rich in silica-alumina microbeads with a nitric acid aqueous solution, controlling the solid content in the mixed slurry to be 30wt% and the nitric acid concentration to be 15wt%, stirring the reaction at a temperature of 70°C for 2.5h, and after the reaction is completed, performing solid-liquid separation, and washing the product with deionized water until it is neutral;
[0065] Step S5: adding the solid material after acid dissolution treatment to a potassium hydroxide aqueous solution for alkaline dissolution reaction, wherein the concentration of the potassium hydroxide solution is controlled at 2.0wt%, the reaction temperature is 40°C, and the reaction time is 5h. After the reaction is completed, solid-liquid separation, washing and drying are performed;
[0066] Step S6: calcining the silicon microbeads after the alkali dissolution treatment at a temperature of 700° C. for 2.5 hours;
[0067] Step S7: Add 40 parts of calcined silica beads, 40 parts of vermiculite, 20 parts of cement, 2 parts of retarder and an appropriate amount of water into a mixer and mix them evenly to obtain a lightweight material mortar.
[0068] Embodiment 3:
[0069] A method for preparing lightweight material mortar from coal gasification slag, comprising the following steps:
[0070] Step S1, selecting a certain amount of coal gasification slag as raw material;
[0071] Step S2: The gasified slag is preliminarily crushed into a particle size of 5-20 mm by a crusher, and then sieved by a vibrating screen to separate the residual carbon with a particle size of more than 10 mm and the silicon-aluminum microbead mixture with a particle size of less than 10 mm;
[0072] Step S3: adding water to the classified gasified slag fine powder to prepare a slurry with a solid content of 18 wt%, stirring at a rotation speed of 2000 r / min for 50 min, and then separating the heavy components (residual carbon and larger particles) and the light components (silica-alumina microbeads) in the slurry by a gravity cyclone separation device to obtain a slurry rich in silica-alumina microbeads;
[0073] Step S4: mixing the slurry rich in silica-alumina microbeads with a hydrochloric acid aqueous solution, controlling the solid content in the mixed slurry to be 15wt% and the hydrochloric acid concentration to be 5wt%, stirring the reaction at a temperature of 50°C for 4h, and after the reaction is completed, performing solid-liquid separation, and washing the product with deionized water until it is neutral;
[0074] Step S5: adding the solid material after acid dissolution treatment to a sodium hydroxide aqueous solution for alkaline dissolution reaction, wherein the concentration of the sodium hydroxide solution is controlled at 0.5wt%, the reaction temperature is from room temperature to 30°C, and the reaction time is 6h. After the reaction is completed, solid-liquid separation, washing and drying are performed;
[0075] Step S6: calcining the silicon microbeads after the alkali dissolution treatment at a temperature of 550° C. for 4 hours;
[0076] Step S7: Add 20 parts of calcined silicon beads, 60 parts of perlite, 15 parts of cement, 0.5 parts of water reducer and an appropriate amount of water into a mixer and mix well to obtain a lightweight material mortar.
[0077] Embodiment 4:
[0078] A method for preparing lightweight material mortar from coal gasification slag, comprising the following steps:
[0079] Step S1: Select a certain amount of coal gasification slag as raw material;
[0080] Step S2: The gasified slag is preliminarily crushed into a particle size of 5-20 mm by a crusher, and then screened by airflow classification technology to separate the residual carbon with a particle size of more than 10 mm and the silicon-aluminum microbead mixture with a particle size of less than 10 mm;
[0081] Step S3: adding water to the classified gasified slag fine powder to prepare a slurry with a solid content of 22 wt%, stirring at a rotation speed of 2200 r / min for 55 min, and then separating the heavy component and the light component in the slurry by a gravity cyclone separation device to obtain a slurry rich in silica-alumina microbeads;
[0082] Step S4: mixing the slurry rich in silica-alumina microbeads with a nitric acid aqueous solution, controlling the solid content in the mixed slurry to be 28wt% and the nitric acid concentration to be 12wt%, stirring the reaction at a temperature of 75°C for 2.8h, and after the reaction is completed, performing solid-liquid separation, and washing the product with deionized water until it is neutral;
[0083] Step S5: adding the solid material after acid dissolution treatment into a potassium hydroxide aqueous solution for alkaline dissolution reaction, wherein the concentration of the potassium hydroxide solution is controlled at 3.0wt%, the reaction temperature is 50°C, and the reaction time is 4.5h. After completion, solid-liquid separation, washing and drying are performed;
[0084] Step S6: calcining the silicon microbeads after alkali dissolution treatment at a temperature of 650° C. for 3.2 h;
[0085] Step S7: Add 45 parts of calcined silica beads, 35 parts of perlite, 15 parts of cement, 2.5 parts of retarder and an appropriate amount of water into a mixer and mix well to obtain a lightweight material mortar.
[0086] Embodiment 5:
[0087] A method for preparing lightweight material mortar from coal gasification slag, comprising the following steps:
[0088] Step S1: Select a certain amount of coal gasification slag as raw material;
[0089] Step S2: The gasified slag is preliminarily crushed into a particle size of 5-20 mm by a crusher, and then sieved by a vibrating screen to separate the residual carbon with a particle size of more than 10 mm and the silicon-aluminum microbead mixture with a particle size of less than 10 mm;
[0090] Step S3: adding water to the classified gasified slag fine powder to prepare a slurry with a solid content of 25 wt%, stirring at a speed of 2500 r / min for 45 min, and then separating the heavy component and the light component in the slurry by a gravity cyclone separation device to obtain a slurry rich in silica-alumina microbeads;
[0091] Step S4: mixing the slurry rich in silica-alumina microbeads with a hydrochloric acid aqueous solution, controlling the solid content in the mixed slurry to be 35wt% and the hydrochloric acid concentration to be 18wt%, stirring the reaction at a temperature of 80°C for 2.2h, and after the reaction is completed, performing solid-liquid separation, and washing the product with deionized water until it is neutral;
[0092] Step S5: adding the solid material after acid dissolution treatment into a sodium hydroxide aqueous solution for alkaline dissolution reaction, wherein the concentration of the sodium hydroxide solution is controlled at 4.5wt%, the reaction temperature is 60°C, and the reaction time is 3h. After the reaction is completed, solid-liquid separation, washing and drying are performed;
[0093] Step S6: calcining the silicon microbeads after the alkali dissolution treatment at a temperature of 720° C. for 2.8 h;
[0094] Step S7: Add 50 parts of calcined silica beads, 30 parts of vermiculite, 15 parts of cement, 3 parts of water-reducing agent and an appropriate amount of water into a mixer and mix well to obtain a lightweight material mortar.
[0095] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing lightweight material mortar from coal gasification slag, characterized in that: The following steps are involved: Step S1, raw material preparation: Selecting a certain amount of coal gasification slag as raw material; Step S2, preliminary crushing and screening: The fumed slag is initially crushed by a crusher to a particle size of 5-20 mm. Subsequently, the crushed fumed slag is classified according to the particle size using a vibrating screen or airflow classification technology to separate larger particles of residual carbon and smaller particles of a mixture of silicon-aluminum microbeads; Step S3, gravity cyclone separation: The classified gasified slag fine powder is added with water to prepare a slurry with a solid content of 15-25wt%, and stirred at a rotation speed of 1800-2500r / min for 40-60min. Then, the slurry is treated by a gravity cyclone separation device to separate the residual carbon and larger particles of the heavy components and the silicon-aluminum microbeads of the light components, so as to obtain a slurry rich in silicon-aluminum microbeads; Step S4, acid dissolution treatment: The slurry rich in silica-alumina microbeads obtained in step S3 is mixed with an appropriate amount of acid solution, the solid content in the mixed slurry is controlled to be 10-40wt%, the acid concentration is 5-20wt%, and the reaction is stirred at a temperature of 50-80°C for 2-4h to remove some metal oxide impurities in the silica-alumina microbeads and leave a mesoporous structure. After the reaction is completed, solid-liquid separation is performed, and the product is washed with deionized water until neutral to remove residual acid solution; Step S5, alkali dissolution to adjust pore size: Add an appropriate amount of alkaline solution to the solid material after the acid dissolution treatment in step S4 for alkaline dissolution reaction, the concentration of the alkaline solution is controlled at 0.1-5.0wt%, the reaction temperature is room temperature to 60°C, and the reaction time is 2-6h to further adjust the pore structure of the microbeads. After the reaction is completed, solid-liquid separation, washing and drying are performed to obtain mesoporous silica microbeads with controllable pore size; Step S6, calcination treatment: The silicon microbeads after the alkali dissolution treatment in step S5 are calcined at a temperature of 550-750° C. for 2-4 hours to remove residual carbon components and improve the purity of the silicon microbeads; Step S7, preparing lightweight material mortar: Add 20-50 parts of the silicon beads calcined in step S6, 30-70 parts of other lightweight aggregates, 10-30 parts of cement, 0.1-5 parts of admixtures, and an appropriate amount of water into a mixer and mix well to obtain lightweight material mortar.
2. The method for preparing lightweight material mortar from coal gasification slag according to claim 1, characterized in that: In step S2, the particle size of the residual carbon is greater than 10 mm, and the particle size of the silica-alumina microbead mixture is less than 10 mm.
3. The method for preparing lightweight material mortar from coal gasification slag according to claim 1, characterized in that: In step S4, the acid solution is one of hydrochloric acid or nitric acid aqueous solution.
4. The method for preparing lightweight material mortar from coal gasification slag according to claim 1, characterized in that: In step S5, the alkaline solution is a sodium hydroxide or potassium hydroxide aqueous solution.
5. The method for preparing lightweight material mortar from coal gasification slag according to claim 1, characterized in that: In step S7, the other lightweight aggregate is one of perlite and vermiculite, and the admixture is one of a water reducing agent and a retarder.